Characterization of a GHF45 cellulase, AkEG21, from the common sea hare Aplysia kurodai - Rahman, Mohammad M.; Inoue, Akira; Ojima, Takao (Frontiers in Chemistry, 2014)
The common sea hare Aplysia kurodai is known to be a good source for the enzymes degrading seaweed polysaccharides. Recently four cellulases, i.e., 95 kDa, 66 kDa, 45 kDa and 21 kDa enzymes, were isolated from A. kurodai (Tsuji et al., PLoS ONE, 8, e65418, 2013). The former three cellulases were regarded as glycosyl-hydrolase-family 9 (GHF9) enzymes, while the 21 kDa cellulase was suggested to be a GHF45 enzyme. The 21 kDa cellulase was significantly heat stable, and appeared to be advantageous in performing heterogeneous expression and protein-engineering study. In the present study, we determined some enzymatic properties of the 21 kDa cellulase and cloned its cDNA to provide the basis for the protein engineering study of this cellulase. The purified 21 kDa enzyme, termed AkEG21 in the present study, hydrolyzed carboxymethyl cellulose with an optimal pH and temperature at 4.5 and 40oC, respectively. AkEG21 was considerably heat-stable, i.e., it was not inactivated by the incubation at 55oC for 30 min. AkEG21 degraded phosphoric-acid-swollen cellulose producing cellotriose and cellobiose as major end products but hardly degraded oligosaccharides smaller than tetrasaccharide. This indicated that AkEG21 is an endolytic -1,4-glucanase (EC 3.2.1.4). A cDNA of 1,013 bp encoding AkEG21 was amplified by PCR and the amino-acid sequence of 197 residues was deduced. The sequence comprised the initiation Met, the putative signal peptide of 16 residues for secretion and the catalytic domain of 180 residues, which lined from the N-terminus in this order. The sequence of the catalytic domain showed 47-62% amino-acid identities to those of GHF45 cellulases reported in other mollusks. Both the catalytic residues and the N-glycosylation residues known in other GHF45 cellulases were conserved in AkEG21. Phylogenetic analysis for the amino-acid sequences suggested the close relation between AkEG21 and fungal GHF45 cellulases.